2017
DOI: 10.3390/molecules22101583
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Phenolic Metabolites from the Edible Fungus Phellinus baumii in LPS-Stimulated RAW264.7 Cells

Abstract: The edible fungus Phellinus baumii Pilat (Hymenochaetaceae) has been used in Korean traditional medicines for strengthening health and prolonging life. An extract of the fruiting bodies of P. baumii was subjected to bioassay-guided fractionation based on its anti-inflammatory effects in lipopolysaccharide (LPS)-stimulated RAW264.7 cells. The resulting fractions were chemically investigated, leading to isolation of three phenolic compounds (1–3), a sesquiterpene (4), two steroids (5–6), a fatty acid (7), and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…To examine the effect of FPGE on NO production in macrophages, we measured nitrite (NO 2 ) level using the Griess Reagent System. Previously, we have shown that LPS induces NO production 18 to 24 h after treatment in RAW 264.7 cells [ 21 22 ]. In this study, we also confirmed the induction of NO production by LPS in the macrophage.…”
Section: Resultsmentioning
confidence: 99%
“…To examine the effect of FPGE on NO production in macrophages, we measured nitrite (NO 2 ) level using the Griess Reagent System. Previously, we have shown that LPS induces NO production 18 to 24 h after treatment in RAW 264.7 cells [ 21 22 ]. In this study, we also confirmed the induction of NO production by LPS in the macrophage.…”
Section: Resultsmentioning
confidence: 99%
“…NF-κB is a transcriptional factor that acts as an important mediator of the immune response and controls the expression of several proteins involved in inflammation, such as iNOS and cyclooxygenase-2 (COX-2) [ 15 ]. To further confirm the anti-inflammatory properties of 1 and 3, we investigated their effects on the protein expressions of NF-κB and iNOS in LPS-induced RAW264.7 macrophage cells using Western blotting; these proteins are involved in the pathogenesis of chronic inflammatory diseases [ 16 ]. Consistent with their inhibitory activity toward NO, compounds 1 and 3 inhibited the induction of iNOS and NF-κB protein expression in a dose-dependent manner [ 11 ] ( Figure 4 , Figure 5 , Figure 6 and Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our ongoing efforts in the discovery of biologically active secondary metabolites from wild Korean mushrooms, we conducted a chemical investigation of C . nipponica and biological evaluation of the isolated compounds .…”
Section: Introductionmentioning
confidence: 99%